MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI EKSPONEN MELALUI MODEL PBL SMAN 4 KISARAN - Surbakti, Muhammad Affan; Syafitri, Ely; Imannur (Universitas Muhammadiyah Metro, 2024)
This research aims to improve students' problem solving abilities in composition and inverse function material using the Problem Based Learning model for students in class X-6 at SMA N 4 Kisaran for the 2024/2025 academic year. The subjects in this research were 36 students in class X-6. This type of research is classroom action research which is carried out in two cycles. The research instruments used in this research were tests and observations. The data analysis technique in this research was carried out qualitatively and the results of the actions were in the form of quantitative scores. This research shows that the average score in the pre-test does not reach the classical completeness percentage, namely only 61.11%. After implementing the problem based learning model, the percentage of post-test completeness in cycle I was 69.45%, so the percentage of completeness had not been achieved, so it continued in cycle II, increasing by 88.89%. Likewise, with student activity, the percentage of student activity in cycle I was 72.22%, then increased in cycle II by 84.67%. Therefore, it can be concluded that the problem based learning model can improve the problem solving abilities and activeness of students in class X-6 of SMA Negeri 4 Kisaran.